EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN PERMAINAN TRADISIONAL CONGKLAK TERHADAP KEMAMPUAN BERHITUNG SISWA - Nurinayah; Firdaus, Andi Mulawakkan; Hadaming, Hamdana (Almeera Education, 2024)
This research identifies students' lack of numeracy skills, particularly in addition and subtraction, as a major problem. Its aim is to assess the effectiveness of using traditional congklak game learning media in improving numeracy skills, learning activities, and student responses in class II of SD Inpres Karunrung Makassar. With a population of all class II students (28 students), the sample was taken using a saturated sampling technique. The instruments used include numeracy tests and documentation. The research results showed a significant increase in students' numeracy skills, active learning activities, and positive responses from students to learning using congklak media. Thus, this media is effective in improving mathematics learning at SD Inpres Karunrung Makassar, with 81.68% of students responding positively to its use.